2005
DOI: 10.1300/j039v08n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Wraparound Services: An Effective Intervention for Families Impacted by Severe Mental Illness

Abstract: Children and families impacted by severe mental illness (SMI) have multiple strains that effect family functioning, child safety, and parental rights. Traditional services for children and families struggling with severe mental illness have not achieved success in improving family functioning and keeping families intact. Wraparound is a philosophy and a system of care with a promising evidence base that could enhance collaboration of child welfare, mental health, and community services to work more effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…It is crucial to develop a philosophy and care system that cooperatively addresses the needs of the whole family. There is now a promising evidence base of effectiveness of wraparound services for families impacted by serious mental illness [ 39 ].…”
Section: Recommendations For Policy Makersmentioning
confidence: 99%
“…It is crucial to develop a philosophy and care system that cooperatively addresses the needs of the whole family. There is now a promising evidence base of effectiveness of wraparound services for families impacted by serious mental illness [ 39 ].…”
Section: Recommendations For Policy Makersmentioning
confidence: 99%
“…Incorporating information about avoiding discrimination into professional training courses may be warranted. Although there is an increasing emphasis on the needs of children with mental health problems [38,39] and a number of innovative approaches to supporting them have been developed [40,41], it is clear from our findings that there is a need for more and better support for these children. Public anti-stigma campaigns can specifically address societal attitudes to parents with mental illness, which may ameliorate some of the discrimination experienced in the social as well as professional spheres.…”
Section: Discussionmentioning
confidence: 93%
“…[6162] Studies also highlight community and home-based interventions-including services that link families with environmental supports and provide access to financial resources and liaison and advocacy services. [636465]…”
Section: Interventions For Families Affected By Parental Mental Illnessmentioning
confidence: 99%
“…[61,62] Studies also highlight community and home-based interventions-including services that link families with environmental supports and provide access to financial resources and liaison and advocacy services. [63][64][65] A recent systematic review reported that preventive interventions with this population lead to significant improvement in parenting behaviors, [66] and a meta-analysis reported positive effects on the children's behavioral and emotional health, with interventions that jointly addressed parents and children yielding larger effects. [67] However, they also pointed out a lack of high-quality studies and recommended adoption of more rigorous research methods to test the interventions [66][67][68]…”
Section: Interventions For Families Affected By Parental Mental Illnessmentioning
confidence: 99%